Europe in Poems : The Versopolis Anthology - McGuinness, Patrick (UK : Arc Publications, 2020)
Aichinger, Renate ; Andova, Nikolina ; Berry, Liz ; Borkovec, Petr ; Brlek, Alen ; Brunner, Helwig ; Buelens, Geert ; Camacho, Carmen ; Capildeo, Vahni ; Cay, Eleni ; Chingonyi, Kayo ; Cirak, Zehra ; Colonna, Valentina ; De Feyter, Moya ; Delville, Michel ; Dintinjana, Veronika ; Dragu, Ana ; Fabias, Radna ; Farrokhzad, Athena ; Fierens, Andy ; Fratus, Tiziano ; Glavas, Marijo ; Gogos, Thanos ; Güzel, Lüfiye ; Habaj, Michal ; Hartnor, Sanna ; Herceg, Monika ; Hopwood, Mererid ; Huseinova, Olena ; Ivankovac, Davor ; Ivory, Helen ; Kalytko, Kateryna ; Karström, Sanna ; Kaziliunaité, Ausra ; Klicka, Barbara ; Kocan, Kristian ; Kruk, Halyna ; Lassaque, Aurélia ; Lleshanaku, Luljeta ; Luka, Eva ; Malek, Natalia ; Mancinelli, Franca ; Martinovski, Vladimir ; Mick, Nino ; Ni Ghriofa, Doireann ; Novakovic, Antonija ; Parmar, Sandeep ; Pedrals, Josep ; Persson, Malte ; Qureshi, Aldo ; Raoul, Lou ; Sandberg McGuinne, J ; Shamugia, Paata ; Sioziou, Danae ; Sobol, Michal ; Sofronieva, Tzveta ; Tsalapatis, Thomas ; Valantinaité, Indre ; Veber, Florjana ; Vogel, Mikael
This anthology showcases sixty poets writing in twenty-five languages form countries across Europe. A feat of European intercultural exchange, it is also a fitting celebration of the Versopolis ethos : an extraordinary variety of themes, styles, and subjects finding common ground in a shared idea of what poetry - and poetry community - can be.
boek